Privacy and dignity in recordkeeping for out-of-home care: a discussion - Jade Purtell; Martine Hawkes (Scottish Journal of Residential Child Care)
This paper provides a preliminary exploration of recordkeeping contexts for young people in residential care experiencing criminalisation and at risk of exploitation. Within the Australian context, the paper explores the potential ramifications of certain recordkeeping processes – notably those of a deficit-based, accusatory or pejorative nature – on a young person's rights to privacy and dignity. An emergent hypothesis questions whether negative sentiments within these records might indirectly precipitate or amplify challenging behaviours that subsequently face criminalisation. While empirical research in this area remains limited, this discussion piece serves as a foundation to instigate conversations and further investigations into the interplay between recordkeeping, identity perception, and behavioural outcomes. As a foray into a relatively uncharted domain, this article aspires to be both a contribution and a call to action for the research community, underscoring the profound significance of records beyond mere administrative utility and their potential role in shaping the lives of children in the care system.